LEGAL REVIEW OF ABUSE OF POWER BY REGIONAL HEADS FROM THE PERSPECTIVE OF CONSTITUTIONAL LAW - Pasrah Kasih Sejati Hulu; Janpatar Simamora; Budiman Sinaga (RADJA PUBLIKA, 2026)
This study aims to examine the legal aspects of abuse of power by regional heads from a constitutional law perspective. Regional heads, as public officials, have limited authority regulated by laws and regulations. However, in practice, it is not uncommon to find regional heads who abuse their authority for personal or group interests, which ultimately harms the public interest and violates the principles of democracy and the rule of law. The method used in this study is a normative legal approach, by examining relevant laws and regulations, such as Law Number 23 of 2014 concerning Regional Government and Law Number 30 of 2014. The results of the study indicate that abuse of power by regional heads constitutes a violation of the principles of accountability, transparency, and the rule of law in the Indonesian constitutional system. Therefore, it is necessary to strengthen the supervisory system and a firm law enforcement mechanism to prevent and prosecute abuse of power by regional heads. This study recommends reformulating the supervisory and guidance policies for regional heads as an effort to strengthen the principles of good governance in the implementation of regional government.